Energy aware routing for efficient green communication in opportunistic networks. Issue 4 (1st July 2019) - Dhurandher, Sanjay K.; Woungang, Isaac; Singh, Jagdeep; Borah, Satya J.
Abstract : Opportunistic networks are characterised by intermittent connectivity, unstable topology, and no assurance of a fixed end‐to‐end path to transfer the messages because of nodes mobility. Due to this, the store‐carry and forward mechanism is used for routing the data in such networks. Considering that the energy of relaying nodes during the routing operation get depleted, there is a clear demand for power‐aware routing schemes for opportunistic networks. This article proposes an energy‐efficient altruism‐based trust‐dependent message forwarding routing protocol for opportunistic networks (called E‐ATDTN), where social matrices are exploited to determine the trustworthiness of a node in participating in the message forwarding procedure. Extensive simulations are conducted to assess the performance of the newly proposed E‐ATDTN protocol against that of the power‐aware PRoPHET, energy efficient PRoWait, and power‐aware EDR protocols showing that E‐ATDTN outperforms E‐PRoPHET, E‐ProWait, and E‐EDR in terms of average residual energy, overhead ratio, dropped messages, and number of dead nodes under varying time‐to‐live, and message generation interval.